Multicolor lineage tracing methods and intestinal tumors - Yanai, Hirotsugu (Springer Japan, 2013)
The generation of chimeras, which is now a standard technology for producing gene modified mutant mice, was originally developed as a tool for developmental biology. However, the application of conventional single marker chimeric mice for developmental study was initially limited. This situation has been dramatically changed by development of multicolor chimeric mice using various kinds of fluorescent proteins. Now using our technology, up to ten different clones could be distinguished by their colors, which enable us to perform more accurate statistical analyses and lineage tracing experiments than by conventional methods. This method could be applied to visualize not only cell turnover of normal stem cells but also cancer development of live tissues in vivo. In the present review, we will discuss how these methods have been developed and what questions they are now answering by mainly focusing on intestinal stem cells and intestinal tumors.